Social and environmental changes due to PT Medco Papua's activities in West Papua - Mandacan, Agustinus; Wurarah, Rully Novie; Baransano, Michael (Economic Military and Geographically Business Review, 2024)
The activities of the company PT Medco Papua Hijau Selaras Capitol Group utilizing the potential of natural resources in producing products have contributed to changing the socio-economic and socio-ecological structure. This research was conducted in Sidey SP-9 District near the PT Medco Papua Hijau Selaras Capitol Group company location area, Manokwari Regency, West Papua Province, which lasted ± 3 months from June to August 2021. The purpose of this study is to determine the impact of the presence of PT Medco Papua Hijau Selaras Capitol Group on the socio-economic and socio-ecological aspects of the Sidey District community of Manokwari Regency. The research used descriptive qualitative and quantitative methods with case study techniques. The results showed that the community's income was above 6 - 10 million, with the most occupation level being company employees. Of the 56 respondents, 40 men and 16 women have the perspective that the presence of the company has an impact on reducing air and water quality. The effects are increased dust, vehicle fumes, factory fumes, and changes in river watercolor and social behavior. Almost 89.28% of respondents responded that air quality decreased, and 65.52% responded that water quality decreased and also changed social behavior. Then, for the Evaluation of the Implementation of Corporate Social Responsibility (CSR), which is carried out only in the supply of electrical energy, participatory planning about customary areas, education skills, and the local economy still needs to be implemented.